Efeito do uso contínuo de um protocolo de polimento mecânico na estabilidade de cor, rugosidade de superfície, microdureza e massa de uma resina acrílica para base de prótese dentária - Melo, Ciro Benevides Falcão (2019)
The acrylic resin, the most widely used material in dental prosthesis, can suffer changes in properties such as color stability, surface roughness, hardness, flexural strength, among others, by the action of several extrinsic factors such as mechanical toothbrushing, contact with chemical agents commonly used for cleaning prosthesis, pigments from food, habits like smoking or alcoholism, as well as intrinsic factors such as the presence of residual monomers. Achieving a satisfactory surface polishing could to control these changes, providing a suitable smoothness for the material, greater patient comfort, lower microbial biofilm accumulation, thus increasing the longevity of prosthetic devices. Objective: This in vitro study evaluated the effect of a continuous mechanical polishing protocol on color stainability, surface roughness, microhardness and mass of an acrylic resin denture base submitted to mechanical toothbrushing, immersion in sodium hypochlorite (NaOCl) 1%, and in coffee. Methods: One hundred square specimens (10 × 10 × 3.5 mm) were divided into 4 groups according to the immersion liquid: (CF - coffee; distilled water in the same immersion period of CF group; HYP - 1% NaOCl; distilled water in the same immersion period of HYP group), and 1 group of mechanical toothbrushing (TB; 71,200 cycles in a brushing simulation machine). Then each group was divided into 2 subgroups (n = 10 per group): exposure to proposed conditions alone or association with mechanical polishing (aluminum oxide polishing paste and a felt wheel coupled to an electric motor, 3000 rpm) in biweekly simulated regime. The surface roughness was evaluated with a portable roughness tester; the color stainability by means of CIEDE 2000 color difference system (ΔE00) with a portable spectrophotometer; microhardness with Knoop microhardness tester, and mass changes in a precision analytical balance. All specimens were evaluated before the exhibitions (T0) and after simulated intervals of 12 (T1) and 24 months (T2) of exposure to the experimental conditions. The data obtained were compared by 2-way ANOVA followed by the Bonferroni post test, considering a significance level of 95%. Results: The polishing protocol significantly influenced the surface roughness (CF and HIP: P<0.0001; ESC: P<0.001) and color stainability (CF: P=0.003; ESC: P=0.008). Significant increase of surface roughness was observed in TB and HYP groups in T2, and the association of the continuous polishing led to a significant reduction of this property in T1, as well as in the CF group. The immersions promoted a significant increase in specimens mass of around 0.7 to 1%, as well as reduction in microhardness. When the polishing was associated, a significant mass loss was observed for these groups (around 1%). The microhardness of TB group also reduced. Higher values of ΔE00 was observed in TB and CF groups, above the clinical perceptibility threshold (>1.30), exceeding the clinical acceptability threshold for CF group (ΔE00>2.25), after 24 months. The polishing reduced the ΔE00 values in these groups, making them comparable to those found after immersion in distilled water. The color change in HYP group was not influenced by the tested polishing. Conclusion: The tested mechanical polishing protocol was able to reduce the damaging effects of mechanical toothbrushing and immersions in 1% NaOCl and coffee solutions, increasing the smoothness of the material, reducing staining caused by immersion in coffee and the color change cause by toothbrushing, without affecting in a clinically relevant manner the microhardness and mass.